Literature and Philosophy in Nineteenth Century British Culture.
1 online resource (313 pages)
Keywords: This is the second volume in a three-volume collection of primary sources which examines philosophy and literature in nineteenth-century Britain. Accompanied by extensive editorial commentary, this collection will be of great interest to students and scholars of British Literature and Philosophy.